State and Peculiarities of Innovation Infrastructure Development in Ukraine - Bocharova, Yu. G. (Statistics of Ukraine, 2018)
The state and peculiarities of the development of the innovation infrastructure of Ukraine were analyzed in the article. It was found that: 1. At the present stage of development of the country, it is difficult to determine the real state and peculiarities of the development of innovation infrastructure, as different institutions provide different, and sometimes diametrically opposed, information on the number of elements of the innovation infrastructure that is created and functioning in Ukraine. 2. Innovation infrastructure of Ukraine is not only fragmentary, but it also shows a steady negative trend of development - the number of elements of innovation infrastructure is constantly decreasing. 3. Innovative funds and companies are the most developed type of innovation infrastructure in Ukraine. 4. The most innovatively active are large (on average 29.2% of surveyed large enterprises) and medium-sized enterprises. 5. The Most Ukrainian innovative enterprises implemented non-technological innovations (implemented marketing and organizational innovations). 6. The vast majority of Ukrainian innovative enterprises with technological innovations engaged in the purchase of machinery, equipment, software and facilities. 7. Only 25% of innovative enterprises with technological innovations co-operated with other enterprises and organizations. 8. Innovative enterprises with technological innovations often collaborated with suppliers of equipment, materials, components or software. 9. Innovative enterprises of Ukraine mostly cooperated with Ukrainian enterprises (on average, 24% of enterprises with technological innovations), on average European enterprises and organizations accounted for 5.7%, China and India – 1.3%, the USA – 1.2%. 10. Innovative activity of enterprises of Ukraine is characterized by clear regional and branch specifics. 11. The vast majority of innovative enterprises carry out their activities in the processing industry, information and telecommunications. 12. The regions-leaders in terms of the share of innovative enterprises in the total number of enterprises are Rivne, Kharkiv and Ivano-Frankivsk region.